Das Eiserne Thor. - Bibliographisches Institut (Hildburghausen) (Hildburghausen : Bibliographisches Institut in Hildburghausen, 1800)
Prikaz jezera okruženog planinama.
Dolje sredina ispod prikaza otisnuto: Das EISERNE THOR. // Bibliograph. Institut in Hildburghausen.
Izvornik digitaliziran
Keywords: Nadorezi